Manajemen Pembelajaran Agama Islam dalam Meningkatkan Mutu Pendidikan pada Dayah Salafiyah Sukma Al-Mubarakah Kunyet Mule - Rahmatillah, Rahmatillah (Medan Resource Center, 2024)
This research aims to describe the management of jurisprudence and aqidah in improving the quality of education at Dayah Salafiyah Sukma al-Mubarakah. Starting from learning planning, organizing, coordinating, controlling and evaluating learning. This research is a qualitative research. The research subjects were school principals, teachers and students. The research location is Sukma Al-Mubarakah Kunyet Mule High School which is located on Jln. Exxon Mobil at the intersection of Cut Mutia's house. Data collection methods in this research are interviews, observation and documentation as well as data analysis using data reduction and presentation techniques. The research results show that Sukma Al-Mubarakah Kunyet Mule High School has carried out learning activities like other high schools in Dayah, but the implementation is not optimal and still requires improvement and improvement in several ways. In the student aspect, better handling is needed, and more organized facilities are arranged. Facilities and infrastructure are the most important things to achieve good quality education. That's where things become obstacles in improving the quality of education.